1995
DOI: 10.1128/iai.63.10.4034-4038.1995
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between maternally derived anti-Plasmodium falciparum antibodies and risk of infection and disease in infants living in an area of Liberia, west Africa, in which malaria is highly endemic

Abstract: In areas where Plasmodium falciparum is endemic, immunoglobulin G is acquired by the fetus in utero, mainly during the third trimester of pregnancy. The potential protective effect of transferred anti-P. falciparum maternal antibodies was examined in a longitudinal study of 100 infants from birth to 1 year of age. The probability of acquiring a P. falciparum infection and developing an episode of clinical malaria was determined in relation to the P. falciparum-specific antibody level of the infant at birth aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…In any case, even in previously exposed individuals, neither natural nor vaccineinduced antibody against (NANP) n is consistently associated with protection (Facer & Tanner 1997). In contrast, both passive transfer and immunization with MSP-1 have conferred protection in animal models (Lew et al 1990, Pouvelle et al 1991 and both in vitro (Blackman et al 1990) and field studies (Egan et al 1996, Hogh et al 1995 have suggested that antibodies against the…”
Section: Discussionmentioning
confidence: 95%
“…In any case, even in previously exposed individuals, neither natural nor vaccineinduced antibody against (NANP) n is consistently associated with protection (Facer & Tanner 1997). In contrast, both passive transfer and immunization with MSP-1 have conferred protection in animal models (Lew et al 1990, Pouvelle et al 1991 and both in vitro (Blackman et al 1990) and field studies (Egan et al 1996, Hogh et al 1995 have suggested that antibodies against the…”
Section: Discussionmentioning
confidence: 95%
“…The results of these two studies are important in that, given the general tendency of antibody levels to be associated with increased risk of infection, any association that contradicts this trend indicates a very significant level of protection. This is particularly true for the Liberian study (38), where antibodies to other malarial antigens were not found to be associated with protection and we can therefore be reasonably sure that the effect of the anti-MSP1 19 antibodies was not confounded by other age-associated factors. In the Kenyan study (37), MSP1 19 was the only antigen examined and we do not therefore know what the general trend would have been.…”
Section: Do Maternal Antibodies Protect Infants From Clinical Malaria?mentioning
confidence: 92%
“…None of the studies using`time to first detected malaria infection' as their primary end point were able to show any protective effect of antimalarial antibodies except that, in one study, children with IgG2 antibodies to crude P. falciparum antigen were less likely to be malaria-slide positive in the first 6 months of life (38). However, this finding has not been replicated in other studies and the authors acknowledge that, given the large number of comparisons made, this one particular finding may have arisen by chance.…”
Section: Do Maternal Antibodies Protect Infants Against Malaria Infecmentioning
confidence: 94%
See 1 more Smart Citation
“…While the results show differences in the prevalence of malaria among adults that correlates with seasonal malaria intensity, the present analyses focused mainly and intentionally upon children as the most sensitive, and critically affected members of the community. However, in contrast to previous studies that grouped children broadly into <2 years (Browne et al 2001) or <5 years (Afari et al 1993) categories, we considered it potentially more revealing to single out the analysis of young infants <6 months because of their congenitally protected status (Pasvol et al 1976;Hogh et al 1995;Shear et al 1996;Branch et al 1998;Kassim et al 2000;Riley et al 2001). Separately, 6-24-month-old children were of special importance because of their higher vulnerability to infection, disease and death (Akanmori et al 1995;Gottschau & Hogh 1995;Hogh et al 1995;Snow et al 1998), and by reason of the large body of previously collected, relevant data with which to compare them (Koram et al 2000;Owusu-Agyei et al 2002).…”
mentioning
confidence: 99%